Engineering and research of rotary tillage combine for potato growing - A. F. Zhuk; Ya. P. Lobachevskiy; V. P. Elizarov; N. Yu. Nikolaenko; S. V. Semichev; S. A. Shishimorov (Сельскохозяйственные машины и технологии)
High-quality soil cultivation for potato planting increases its productivity and allows to reduce damageability of tubers when harvesting. At its growing intensive complete or strip soil pulverizationl, formation of ridges or seedbeds for planting and growing are required. For performance of each method machines of different type, including various tillers, tilling ridge or seedbed formers, are used. The authors offered a multipurpose tiller with the horizontal rotor aggregated with tractors of classes 1.4 and 2. At readjustment the tiller operatest the main methods of soil cultivation necessary at potato growing: complete prelanding tilling, ridges or seedbeds formation for planting, cultivation of them at care of seedlings, loosening of an underlying layer in strips of the formed ridges or seedbeds under planting rows. This tiller has some constructional features: the tiller rotor with removable sections of flat L-shaped teeths allowing to operate complete and strip soil cultivation at a depth of 12 cm; the disk furrow shaperы regulated on depth and operating width; removable hoes for loosening of the lower layer of soil at depth of 22 cm under planting rows; a replaceable deflector with a direct back edge and (or) with a removable furrow shapers; basic wheels movable from a forward girder onto sidewalls behind - when seedbeds forming. The authorsreport the main agrotechnical requirements to the methods of complete prelanding tilling, ridges and seedbeds forming which are carried out by a tiller and cultivation of them when planting. The tiller has different complete set options for performance of these methods. Use of the offered tiller provides high-quality performance of methods of soil cultivation and potato growing and by 2-3 times reduces a range of necessary machines and costs of acquisition of them.